Gender differences in the moderating capacity of reserve and resilience factors on the association of Alzheimer's disease brain pathology and cognitive function. (31st December 2021) - Udeh‐Momoh, Chinedu T; Zheng, Bang; Price, Geraint J; de Jager, Celeste A; Robb, Catherine; Watermeyer, Tam J; Toopchiani, Sima T; Ford, Jamie; Su, Bowen; Giannakopoulou, Parthenia; Saad, Ziad S.; Fogle, Michael; et al.
Abstract: Background: In the context of ageing and Alzheimer's disease (AD), factors linked to reserve and resilience may confer protection against impact of underlying neuropathology on cognitive function. Such factors are differentially manifested in men and women, yet limited studies have explored potential divergence in their capacity to moderate cognitive outcomes, particularly within at‐risk preclinical populations. Here we evaluate gender dichotomies in the effect modification of independent brain and cognitive reserve factors on associations of AD‐related neuropathology and cognition. Method: Gender‐stratified analysis of CHARIOT:PRO SubStudy data (2, 451 preclinical older adults: 60‐85 years, screened at Imperial College London and University of Edinburgh) was performed using a‐priori confounder‐adjusted linear regression models. The effect modifying role of brain (intracranial volume) and cognitive (educational attainment, estimated premorbid‐intelligence: epIQ, physical activity) reserve proxies on the associations of AD neuropathology (brain amyloid load: via PET/CSF Aβ42; and hippocampal volumes: structural MRI) with multidomain cognitive performance (assessed via learning effect [i.e. difference in initial administration and baseline scores – median 3.5 months] on the Repeatable Battery Assessment of Neuropsychological Status‐RBANS) were independently examined in men and women. Result: Learning effects were negatively modulated by amyloid positivity and male gender. Larger hippocampal volumes predicted better global cognition in men, and better immediate memory for both men and women (All P‐values<0.05). In mutually adjusted models (additionally accounting for age and ApoE), education and physical activity modified the effects of amyloid positivity on cognition, while epIQ moderated associations with hippocampal volume. The moderation was more pronounced for highly physically active men (β=7.7; p=0.04) and marginally for women educated to Bachelors' level (β=5.9; p=0.06). Above‐median epIQ moderated associations of hippocampal volume with global cognition only in women (β=0.0003; p=0.03). Adjustment for BMI, smoking, blood pressure and diabetes had no remarkable effect on the results. Conclusion: We noted differential effects of cognitive reserve in men and women supporting the importance of accounting for sex/gender divergence when exploring moderators of AD‐related neuropathology on function. Further research into mechanisms underlying sex/gender differences in preservation and maintenance of cognitive function are warranted for personalised strategies towards increasing neurocognitive resilience and delaying transitions to more severe clinical states.